(untitled) - Herodotus (New York, 1942)
Selections from Herodotus' History which follow the events of the great war between the Greeks and the Persians. The translated extracts include Herodotus' descriptions of the preparations for war and of the great land- and sea-battles which took place. Linking commentaries explain Greek and Persian strategies and battle manoeuvres. Background information on the ships and on the soldiers fighting in the war is also given.
Keywords: History, Ancient,Lịch sử cổ đại